2019
DOI: 10.1177/2474126419865990
|View full text |Cite
|
Sign up to set email alerts
|

Fellow-Eye Conversion and Treatment in Exudative Age-Related Macular Degeneration

Abstract: Purpose: This article assesses anatomical and visual outcomes after intravitreal antivascular endothelial growth factor (anti-VEGF) treatment in fellow eyes with wet age-related macular degeneration (AMD). Methods: A retrospective chart review was conducted of 349 patients diagnosed with wet AMD between 2005 and 2017 at a single academic institution. Initial diagnosis of unilateral wet AMD and a minimum follow-up time of 1 year after diagnosis were required for inclusion. Individuals were excluded if the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…For example, retrospective studies of patients monitored by OCT found that one half of patients with unilateral diabetic macular edema (DME) and 20% to 30% of patients with unilateral exudative AMD develop fellow-eye involvement over 2 years. [4][5][6][7] The fellow eye often has a decreased treatment burden and better visual outcomes than the initial eye, which may be attributed to more frequent surveillance and early diagnosis and treatment. 7 Following are some practical guidelines to consider toward making the most of the more commonly available multimodal imaging in the approach to diagnosing and treating medical and surgical retinal diseases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, retrospective studies of patients monitored by OCT found that one half of patients with unilateral diabetic macular edema (DME) and 20% to 30% of patients with unilateral exudative AMD develop fellow-eye involvement over 2 years. [4][5][6][7] The fellow eye often has a decreased treatment burden and better visual outcomes than the initial eye, which may be attributed to more frequent surveillance and early diagnosis and treatment. 7 Following are some practical guidelines to consider toward making the most of the more commonly available multimodal imaging in the approach to diagnosing and treating medical and surgical retinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The fellow eye often has a decreased treatment burden and better visual outcomes than the initial eye, which may be attributed to more frequent surveillance and early diagnosis and treatment. 7 Following are some practical guidelines to consider toward making the most of the more commonly available multimodal imaging in the approach to diagnosing and treating medical and surgical retinal diseases. This review is not exhaustive but rather is designed to provide practical guidance to the practicing clinician.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations